6102 SAYILI TÜRK TİCARET KANUNU'NUN 1484. MADDESİNE GÖRE ZORUNLU SORUMLULUK SİGORTASINDA SİGORTACININ ZARAR GÖRENE KARŞI İFA YÜKÜMLÜLÜĞÜ - (:unkn) unknown (My University, 2012)
6102 sayılı TTKnun Zarar Görene Karşı İfa Yükümlülüğü başlığını taşıyan 1484. maddesine göre, zorunlu sigortada sigortacı, sigortalısına karşı ifa yükümlülüğünden kısmen veya tamamen kurtulmuş olsa bile, bu hususu zarar görene karşı ileri süremez. TTK m.1484 hükmü, TTK m.1486/f.2ye göre aksine şartın geçersiz sayıldığı emredici bir hükümdür. Bu düzenlemenin kaynağı olan § 158c a.F.VVG hükmü, 01.01.2008 tarihinde yürürlükten kalkmış ve yerine § 117 VVG hükmü getirilmiştir. Ne var ki TTK m.1484 hükmü, kaynak kanundaki değişikliği takip etmemiştir. Sigortacının zarar görene karşı ifa yükümlülüğü, zorunlu sigorta bedeli miktarıyla sınırlandırılmıştır. Buna karşılık sigortacının TTK m.1484e göre ifa yükümlülüğünün zorunlu sigortada üstlenilen riskler ve ifa yükümlülüğünün zamanaşımı süresiyle de sınırlı olması gerekir. TTK m.1484 de sigortalısına karşı ödeme yükümlülüğü ortadan kalktığı halde, kanun hükmüyle zarar görene ödemek zorunda kalan sigortacının, bu ödemeden sonra zarar görene halef olarak sigortalıya rücu edebileceğine ilişkin bir açıklamaya yer verilmemesi, önemli bir eksikliktir. TTK m.1484/f.2ye göre, sigorta sözleşmesinin sona ermesinin yetkili makama bildirilmesinden bir ay sonra sigortacının zarar görene karşı sorumluluktan kurtulabilme imkanı getirilmiştir. Ancak maddede veya diğer bir düzenlemede yetkili makamın neresi olduğu hususu açıklanmamıştır. Ayrıca sona ermeye § 117 VVG de olduğu gibi sözleşmenin yokluğu ve sürenin sona ermesi hallerinin de dahil olması gerekir. TTK m.1484/f.3 de, zararın SGK tarafından karşılandığı ölçüde sigortacının sorumluluktan kurtulacağı öngörülmüştür. Buna karşılık § 117 VVG de öngörüldüğü gibi zarar görenin zararının bir diğer zarar sigortasından karşılandığı ölçüde de sigortacının TTK m.1484e göre ifa yükümlülüğünün sona ermesi gerekir.

According to article 1484 of Turkish Commercial Code No. 6102 titled " Obligation to pay to the inj ured party ", even though insurer is exempted partially or f ully f rom the obligation to pay against policy owner, this matter cannot be p roposed in a case against an inj ured party since the article 1484 of TCC is a mandatory clause under the guarantee of article 1486/f .2 and, as a result, any p rovision contrary is considered null and void. Provision § 158c a.F.VVG which was the source of this regulation has been revoked on 01.01.2008 and replaced by §117 VVG. However, this particular change in the source was not pursued by article 1484 of TCC. Insurer's obligation to pay against inj ured party is restricted to the amount of the compulsory insurance. According to article 1448 of TCC, insurer's obligation to pay should also be limited by the risks assumed with compulsory insurance and limitations period. Although not obligated to pay against policy owner in article 1484 of TCC insurer is put under an obligation by a legal p rovision to pay against inj ured party, thus absence of an explanation should be considered as an important def iciency concerning insurer's ability to claim against policy owner by subrogation once the payment to inj ured party is made... insurer's obligation to pay according to article 1484 of TCC should come to an end. According to article 1484/f .2 of TCC, an opportunity is introduced that insurer will be exempted f rom all obligations against inj ured party af ter one month f ollowing the notif ication of the end of insurance contract to a responsible authority. However, there is no explanation existed in ref erred article or in any other regulation regarding the identity of a responsible authority. Furthermore, j ust like in § 117 VVG, such cases like non-existence of a contract and exp iration should also be included to the ending of an insurance contract. Article 1484/f .3 anticipated that the insurer will be exempted f rom all obligations as long as the damage is compensated by Social Security Institution. Correspondingly, as anticipated in § 117 VVG, insurer's obligation to pay according to article 1484 of TCC should also come to an end in a case where the damage to inj ured party is compensated by another indemnity insurance.
Keywords: Hukuk